Mass mortalities of oysters (Crassostrea gigas) during spring 1988 in the Bay of Marennes-Oleron, related to environmental conditions - Bodoy, Alain; Garnier, Jacqueline; Razet, Daniel; Geairon, Philippe (ICES-CIEM CM 1990 / K:11, 1990)
Mass mortalities of oysters were recorded in the South of the Bay of Marennes-Oleron, during spring 1988. The percentages of mortality averaged 50 % and reached up to 90 % in some areas of bottom culture. The losses were estimated to 7 800 tonnes. This paper present the results of the investigations carried out in several fields. Among them, pathological examination revealed that no pathogenic agent or parasitic infestation could be evoked to explain these mortalities. Analyses of pollutants were either negatives, or the concentrations were far below the toxicity levels. Climatological and hydrological observations showed that rainfalls were twice more abundant then the average, for a period of 6 months preceding the mortalities. The salinity was low and fluctuating in the area, and the temperature was warmer, then the average during the same period. Phytoplanktonic blooms were recorded only by the end of May, latter then usual. These ecological changes resulted in a poor physiological condition of the oysters, which became critical for the grounds located at the South of the bay. Both their high tidal position and low quantities of phytoplankton are characteristic of this area. The high densities of oysters in the parks were also evoked as contributing to the establishment of such critical conditions.